2020
DOI: 10.1002/rcm.8955
|View full text |Cite
|
Sign up to set email alerts
|

Determination of intracellular anlotinib, osimertinib, afatinib and gefitinib accumulations in human brain microvascular endothelial cells by liquid chromatography/tandem mass spectrometry

Abstract: Rationale Brain metastases are a common complication in patients with non‐small‐cell lung cancer (NSCLC). Anlotinib hydrochloride is a novel multi‐target tyrosine kinase inhibitor (TKI) exhibiting a superior overall response rate for brain metastases from NSCLC. The penetrability of anlotinib and three generations of epidermal growth factor receptor (EGFR) TKIs (osimertinib, afatinib and gefitinib) into brain microvascular endothelial cells (HBMECs) was compared. Methods A sensitive quantification method for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Currently, anlotinib has been approved by China National Medical Products Administration for the treatment of nonsmall‐cell lung cancer (NSCLC), small cell lung cancer, soft tissue sarcoma, and medullary thyroid cancer. In addition, anlotinib could cross the BBB confirmed by in vivo experiments and advanced NSCLC with brain metastasis 21 . On the other hand, radiotherapy could increase the permeability of blood–brain barrier and increase anlotinib concentration in brain tissue.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Currently, anlotinib has been approved by China National Medical Products Administration for the treatment of nonsmall‐cell lung cancer (NSCLC), small cell lung cancer, soft tissue sarcoma, and medullary thyroid cancer. In addition, anlotinib could cross the BBB confirmed by in vivo experiments and advanced NSCLC with brain metastasis 21 . On the other hand, radiotherapy could increase the permeability of blood–brain barrier and increase anlotinib concentration in brain tissue.…”
Section: Introductionmentioning
confidence: 83%
“…Previous studies reported favorable responses in NSCLC patients with brain metastases, demonstrating its ability to control brain tumors and survival. 22,47 Furthermore, Ma et al 21 confirmed optimal penetration of anlotinib into brain microvascular endothelial cells, potentially overcoming the limited drug concentration in brain tumors due to the blood-brain barrier (BBB). These findings suggest that anlotinib is a promising candidate for treating intracranial malignant tumors.…”
Section: Ta B L Ementioning
confidence: 98%
See 1 more Smart Citation
“…There were studies that revealed that anlotinib potentially inhibits more targets and is superior to other antiangiogenesis drugs such as sunitinib, sorafenib and nintedanib both in vitro and in vivo [7]. Another confirmed advantage of anlotinib includes the better penetration of brain microvascular endothelial cells than other TKIs, including osimertinib, afatinib and gefitinib [16]. Compared with other common VEGFR-TKIs, anlotinib was reported to have a lower incidence of grade 3/4 adverse effects, which include thrombocytopenia, neutropenia including, hypertension, hand-foot syndrome, diarrhea, stomatitis and anorexia [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In the future, with the promise of highly specific, possibly mutation-specific drugs, it will be possible to develop personalized drug treatments targeted to the molecular constitution of individual tumors [225]. In addition, state-of-the-art technologies, such as liquid chromatography coupled to tandem mass spectrometry, currently capable of simultaneously measuring multiple drugs in cell extracts [226], could also be adopted for in vivo follow-ups of specific drugs' uptakes in both primary and metastatic tumors, to better dose therapeutic treatments in a personalized manner.…”
Section: Open Questions In Treatment Strategiesmentioning
confidence: 99%